Upaya mendalami arti lambang PMI untuk meningkatkan minat generasi muda pada organisasi PMI - Ani Anjarwati; Malqa Dewi Royyana; Rr Ghina Ayu Putri Tya Kunanti; Ika Putri Fadilah; Devi Puspita; Moch. Abdul Azis (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2022)
The Indonesian Red Cross (PMI) is a national association organization in Indonesia that was founded by Dr. RCL Senduk and Bahder Djohan to engage in social humanitarian activities. PMI has always adhered to the seven basic principles of the International Red Cross and Red Crescent movements, namely humanity, equality, volunteerism, independence, unity, neutrality, and universality. The Indonesian Red Cross in its implementation does not make a distinction but prioritizes the victims who need immediate help for their lives. The PMR is under the supervision of the PMI, whose objectives are not much different from the PMI. PMR became important and became one of the extracurricular organizations in the school because its existence became one of the bridges with health workers to save more people. Unfortunately, our society still does not understand how important the handling and provision of P3K is not only at home but also outside the home or in the bag. Make the community aware through the younger generation of the importance of rescue and handling so that the chances of life of the patient, or in medical terms commonly called the "golden hour", on the victim are not missed.